2016
DOI: 10.1016/j.ekir.2016.08.007
|View full text |Cite|
|
Sign up to set email alerts
|

Lipidomic Signature of Progression of Chronic Kidney Disease in the Chronic Renal Insufficiency Cohort

Abstract: Introduction Human studies report conflicting results on the predictive power of serum lipids on progression of chronic kidney disease (CKD). We aimed to systematically identify the lipids that predict progression to end-stage kidney disease. Methods From the Chronic Renal Insufficiency Cohort, 79 patients with CKD stage 2 to 3 who progressed to ESKD over 6 years of follow up were selected and frequency-matched by age, sex, race, and diabetes with 121 non-progressors with less than 25% decline in estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 54 publications
4
71
1
Order By: Relevance
“…Specific fragmentation in MS2 allows accurate identification of unique lipids in MS1 as described previously. [32, 41] Figure 4 (ESM Table S1) shows that 277 lipids species in the LDL fraction and 278 species in the HDL fraction are identified in UC-prepared samples in positive MS mode. Similarly, 141 lipids in both LDL and HDL fractions are found in UC-prepared samples in negative mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific fragmentation in MS2 allows accurate identification of unique lipids in MS1 as described previously. [32, 41] Figure 4 (ESM Table S1) shows that 277 lipids species in the LDL fraction and 278 species in the HDL fraction are identified in UC-prepared samples in positive MS mode. Similarly, 141 lipids in both LDL and HDL fractions are found in UC-prepared samples in negative mode.…”
Section: Resultsmentioning
confidence: 99%
“…[32] In brief, the modified Bligh-Dyer method[33] is used to prepare samples. The lipoprotein fractions collected by SP-AF4 and lipoproteins isolated by UC are brought to room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…In a human study comparing healthy controls and CKD patients, Reis et al found that the content of total PC and Ceramides were decreased along with the ratio of LPC/LPE(18). In a study comparing patients with CKD progression compared to control patients, Afshinnia et al reported that CKD progression was associated with lower Cholesteryl ester (CE), diacylglycerols (DG), PC, plasmenylcholine (PC-P), PE-P, and phosphatidic acid (PA), and elevated PE and monoacylglycerols (MAG)(19). This finding suggests that patients with CKD progression with a decrease of longer acyl chains and polyunsaturated lipids might benefit from the effects of polyunsaturated fatty acid supplementation, as some previous studies have suggested(20,21).…”
Section: Discussionmentioning
confidence: 99%
“…High‐throughput multi‐omics approaches (transcriptomics, proteomics, metabolomics and lipidomics) have been used to profile patients' biospecimen (kidney biopsy, plasma and urine samples). These multi‐omics data sets contributed to the discovery of biomarker candidates that are associated with disease progression . Table includes molecular biomarkers that were discovered using systems biology approaches with demonstrated association with kidney outcomes in patient‐related studies.…”
Section: The Use Of Systems Biology Approach To Identify Patients Atmentioning
confidence: 99%
“…These multiomics data sets contributed to the discovery of biomarker candidates that are associated with disease progression. 17,[22][23][24][25][26][27][28][29] Table 2 includes molecular biomarkers that were discovered using systems biology approaches with demonstrated association with kidney outcomes in patient-related studies.…”
Section: The Identification Of Novel Molecular Markers Associated Wmentioning
confidence: 99%